Data sources for in vivo molecular profiling of human phenotypes. (7th September 2016) - Cardozo, Timothy; Gupta, Priyanka; Ni, Eric; Young, Lauren M.; Tivon, Doreen; Felsovalyi, Klara
Abstract : Molecular profiling of human diseases has been approached at the genetic (DNA), expression (RNA), and proteomic (protein) levels. An important goal of these efforts is to map observed molecular patterns to specific, mechanistic organic entities, such as loci in the genome, individual RNA molecules or defined proteins or protein assemblies. Importantly, such maps have been historically approached in the more intuitive context of a theoretical individual cell, but diseases are better described in reality using an in vivo framework, namely a library of several tissue‐specific maps. In this article, we review the existing data atlases that can be used for this purpose and identify critical gaps that could move the field forward from cellular to in vivo dimensions. WIREs Syst Biol Med 2016, 8:472–484. doi: 10.1002/wsbm.1354 This article is categorized under: Biological Mechanisms > Chemical Biology Laboratory Methods and Technologies > Genetic/Genomic Methods Laboratory Methods and Technologies > Proteomics Methods